The Long and Short of Environmental Solutions. Issue 2 (20th March 2017) - Kareiva, Peter; Fuller, Emma
Abstract: Capitalism, globalization, consumerism and an almost religious commitment to perpetual growth are often blamed for the world's environmental woes. But does this mean that economic stagnation and Marxism, for example, would be the friend of the environment? We need to analyze the flaws of our current socioeconomic ecosystem and work to make concrete improvements. Some improvements are short term and simply reflect improved 'best practices' and more flexible frameworks for implementing existing policies. These improvements can make a difference in a matter of years and are relevant to the urgency of avoiding species extinctions in the near term. These changes are analogous to 'tuning' a car's engine. Other improvements will require fundamental changes in how our economic system works – changes such as breaking the reliance of developing nations on cheap fossil fuels. These changes are analogous to rebuilding and redesigning a car's engine. But whatever actions are explored, they must be practical and concrete. Bemoaning the avarice and resource exploitation of capitalism and its addiction to growth is a, by‐now, stale and unactionable critique of the modern world. Abstract : Evidence indicates that democracy, respect for human rights, absence of corruption and good governance in general, all tend to facilitate environmental improvements—just as they promote improvements in all sectors.